A review on antimicrobial botanicals, phytochemicals and natural resistance modifying agents from Apocynaceae family: Possible therapeutic approaches against multidrug resistance in pathogenic microorganisms. (July 2020) - Anand, Uttpal; Nandy, Samapika; Mundhra, Avinash; Das, Neela; Pandey, Devendra Kumar; Dey, Abhijit
Graphical abstract: Abstract: Accelerated emergence of drug- resistant pathogenic microbes, their unbeatable virulence and a gradual loss of efficacy of currently used antimicrobial agents over the last decade, have expanded the scope of herbal medicine to combat this emerging challenge to have a wide spectrum of activity to develop effective medicines with lesser untoward side effects. Plant-based natural products should be of utmost interest to today's pharmaceutical industries since they are a primary source of new chemical entities directed at new drug targets. Apocynaceae or 'Dogbane' family has attained a global reputation as a source of some life-saving plant-derived products and novel compounds. Members of this family have also been extensively investigated against several nosocomial pathogenic microbes through in vitro and in vivo experimental settings. Several plant-derived components obtained from members of this family have also exhibited remarkable microbial growth inhibitory properties. Popular and widely accepted international databases such as PubMed, Science Direct, ResearchGate, Scopus, Google Scholar, JSTOR and more were searched using the various search strings such as Apocynaceae, antimicrobials, multidrug resistance, resistance modifying agents and pathogenic microorganisms were used in various combinations to retrieve several citations related to the topic. The current review encompasses recent developments in experimental studies and phytochemical analyses which correlates with antimicrobial efficacy of selected Apocynaceous plants along with synergistic mechanism and structural details. The present review recognizes and leverages the importance of Apocynaceae plants, which could be of significant interest in the development of more effective and less toxic antimicrobial drugs which may surmount multidrug resistance. Three different paradigm models harnessing clinical antimicrobial resistance (AMR) including the plant family Apocynaceae, Gram-positive and Gram-negative bacterial species have been broadly discussed in this review. In a nutshell, the present review represents a comprehensive account on the antimicrobials and resistance modifying agents obtained from the members of the plant family Apocynaceae and derived phytochemicals. It also gives an insight into the underlying mode of action of these phytochemicals against an array of pathogenic bacteria, their mechanism of antibiosis, plant parts from which the phytochemicals were isolated or the extracts was prepared with a critical discussion on the botanically-derived antibiotics as a template for antimicrobial drug development.